Modlitwa za wiernych zmarłych w modlitewnikach przełomu XX i XXI wieku. Obecność, tytuł, lokalizacja - Żmigrodzka, Bożena (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2018)
The article is about the Polish version of Prayer for the Faithful Departed (Latin: Oratio pro fidelibus defunctis) in the contemporary prayer books. In the introduction, the origins of the text were described and the multitude of contexts it appears in was pointed out. Subsequently, its presence/absence in the prayer collections, surfacing titles and placement in differently profiled prayer book chapters were discussed.